Productivity Analysis Of Coffee Production Process With Objective Matrix (Omax) Method (The Case Study at PT. Perkebunan Kandangan, Pulosari Panggungsari, Madiun) - Ma'ruf Pambudi Nurwantara; Panji Deoranto; Mas’ud Effendi (Warmadewa University Press, 2018)
Production activities each company are expecting the creation of productivity. This research was aims to determine levels of total and partial productivity by using Objective Matrix and propose improvements. The study was conducted at Perkebunan Kandangan Pulosari Panggungsari plantations began from January to April 2015. The data gathered consist of secondary data and primary data. Elements analyzed the productivity of human, machine, wood fuel and diesel fuel. The results showed that the value of productivity was experiencing fluctuating, the value of total productivity in the processing of coffee by 6.660. Partial productivity value on the human element of 1.635, 1.463 for labor, fuelwood amounted to 1,162, working hours standing to 0.894 generator engines and diesel fuel of 1.49. Proposed improvements that can be done by optimizing the number and performance of every element of productivity.